2017
DOI: 10.7554/elife.25257
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-mediated gating of Cdc42 signalling flux

Abstract: Scaffold proteins modulate signalling pathway activity spatially and temporally. In budding yeast, the scaffold Bem1 contributes to polarity axis establishment by regulating the GTPase Cdc42. Although different models have been proposed for Bem1 function, there is little direct evidence for an underlying mechanism. Here, we find that Bem1 directly augments the guanine exchange factor (GEF) activity of Cdc24. Bem1 also increases GEF phosphorylation by the p21-activated kinase (PAK), Cla4. Phosphorylation abroga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 45 publications
(70 reference statements)
6
63
0
Order By: Relevance
“…Surprisingly, we report that active Cdc42 is not sufficient to recruit Scd1 in the absence of Gef1. While it has been proposed that Cdc42 establishes positive feedback through the formation of the ternary complex consisting of the Cdc42 effector PAK (p21-activated kinases) and its associated scaffold protein (Scd2 or Bem1) (Butty et al, 2002;Kozubowski et al, 2008), studies in S. pombe and S. cerevisiae suggest that Pak1 kinase activity antagonizes either the Cdc42 scaffold or the GEF, rather than establishing a positive feedback (Das et al, 2012;Gulli et al, 2000;Kuo et al, 2014;Rapali et al, 2017). In support of this antagonistic role of Pak1, we find that more Scd1 accumulates at cell ends and at the division site in the pak1 switch-off mutant.…”
Section: Multiple Gefs Combinatorially Regulate Cdc42 During Complex mentioning
confidence: 99%
“…Surprisingly, we report that active Cdc42 is not sufficient to recruit Scd1 in the absence of Gef1. While it has been proposed that Cdc42 establishes positive feedback through the formation of the ternary complex consisting of the Cdc42 effector PAK (p21-activated kinases) and its associated scaffold protein (Scd2 or Bem1) (Butty et al, 2002;Kozubowski et al, 2008), studies in S. pombe and S. cerevisiae suggest that Pak1 kinase activity antagonizes either the Cdc42 scaffold or the GEF, rather than establishing a positive feedback (Das et al, 2012;Gulli et al, 2000;Kuo et al, 2014;Rapali et al, 2017). In support of this antagonistic role of Pak1, we find that more Scd1 accumulates at cell ends and at the division site in the pak1 switch-off mutant.…”
Section: Multiple Gefs Combinatorially Regulate Cdc42 During Complex mentioning
confidence: 99%
“…At the cell pole in wild-type cells, Cdc42 displays reduced diffusion compared with elsewhere on the plasma membrane, reflecting activation of Cdc42 at the cell pole (Slaughter et al, 2013;Sartorel et al, 2018). Previous work from our laboratory demonstrated that Bem1, which boosts Cdc42 activation (Rapali et al, 2017), and PS, which recruits Cdc42 activators, contribute to the reduced diffusion and nanoclustering of Cdc42 at the pole (Sartorel et al, 2018). We therefore reasoned that the reduced rate of Cdc42 diffusion and its nanoclustering at the pole may be linked to the lipid interactions exhibited by the Bem1 BC motifs.…”
Section: Scaffold Tethering To Anionic Lipids Affects Cdc42 Dynamics mentioning
confidence: 82%
“…We mutated each cluster individually or all 14 residues simultaneously ( Fig 3A). This FRET-based mant-GTP loading assay serves as a sensitive readout for Bem1 function, since Bem1 boosts GEF activity via interactions with Cdc24 and Cdc42 that are distinct from the N-terminal BC motifs (Ito et al, 2001;Yamaguchi et al, 2007;Rapali et al, 2017). Of the three clusters of basic residues, the most N-terminal BC-1 cluster appeared to be the most important ( Fig 3B).…”
Section: Identification Of a Robust Anionic Lipid Targeting Sequence mentioning
confidence: 99%
See 2 more Smart Citations